MASALAH UPAH DI JAWA: DARI SRIHARJO TAHUN 1960-AN KE TANGERANG TAHUN 1990-AN* - Chris Manning (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1996)
The results of the PJPI reject the findings of earlier researches about the concept of disguised unemployment. In the context of the carrying capacity of the natural resources of a place compared with the existing population, its relationship with poverty is no longer very strong. Srihardjo is one of the villages in the island of Java which disagrees with this concept, where by the limited supply of the agricultural land can perfectly be substituted with the labor market in the industrial sector. However, the impact of the economic structural transformation at this time has got a balance on the wage dimension in the non-agricultural sector, particularly among the industrial workers, and the workers in the informal sector. This issue has the inevitable consequence of the exploitative tendency of the employers or entrepreneurs, and lack of support for the labor unions, which places them in a weak bargaining position in efforts to have their wages raised. Chris Manning in his paper shows the impact of the economic structural transformation on the production of workers, and their level from the agricultural sector (Srihardjo) to an industrial sector (Tangerang).